Factors contributing to workplace violence: A study in the fleet supply depots in Malaysia - Chew Abdullah, Nor Azimah; Ali, Anizan (2012)
This study is to study the relationship between management style, working environment, and coworkers’relationships with workplace violence in Fleet Supply Depots (FSD) and how the coworkers’ relationships in the organization have an impact on the FSD personnel.The primary focus of this study is to provide an empirical basis that could help the management in the formulation of guidelines, and to improve working procedures to overcome any cases of workplace violence happening in FSD.Data was gathered through questionnaires distributed among 155 respondents who were FSD staff who served in various departments in FSD. However, only 150 questionnaires were returned for analysis and that gave a 96.77 percent rate of response.The data was analyzed using the Statistical Package for Social Sciences (SPSS) version 17.0. Findings showed that there was not a significant difference in co-workers’ relationships between male and female staff in FSD.There is a positive correlation between co-workers’ relationship and management style except for working environment.It was seen that co-workers’ relationships and working environment influence the changes in workplace violence.Future studies could be extending to other factors like family violence to see its influence on workplace violence.